Una nueva variedad de Centrosema macrocarpum Benth. (Leguminosae: Papilionoideae) de los andes colombianos - Schultze-Kraft, Rainer; Belalcázar G., Javier (1995)
A new variety of Centrosema macrocarpum is described. It occurs only in Colombia, mainly an intermediate altitudes (1000-2000 m) in the Andes and the Sierra Nevada de Santa Marta. Diagnostic features of the variety are the reddish colour of young leaves, the purple-violaceous colour of the corolla, and the unusually large pods and seeds